Peering into the Heart of Darkness with VLBA: Radio-quiet Active Galactic Nucleus in the JWST North Ecliptic Pole Time-domain Field - Payaswini Saikia; Ramon Wrzosek; Joseph Gelfand; Walter Brisken; William Cotton; S. P. Willner; Hansung B. Gim; Rogier A. Windhorst; Vicente Estrada-Carpenter; Ivan Yu. Katkov; Ingyin Zaw; Michael J. Nicandro Rosenthal; et al. (The Astrophysical Journal)
We present initial results from the 4.8 GHz Very Long Baseline Array (VLBA) survey of the JWST North Ecliptic Pole Time-Domain Field (TDF). From 106 radio sources found in the Karl G. Jansky Very Large Array (VLA) observations in the TDF, we detected 12 sources (∼11% detection rate) at ∼3.3 μ Jy rms sensitivity and ∼4 mas resolution. Most detections exhibit parsec-scale emission (less than 40 pc) with high VLBA/VLA flux density ratios and brightness temperatures exceeding 10 ^5 K, confirming nonthermal active galactic nucleus (AGN) activity. Spectral indices α  ≳ −0.5 correlate with higher VLBA/VLA flux ratios, consistent with synchrotron emission from AGN coronae or jets. In the majority of our sources, star formation contributes less than 50% of the total VLBA radio emission, with a few cases where the emission is almost entirely AGN driven. Although the radio emission from radio quiet AGN is thought to be primarily driven by star formation, our VLBA observations confirm that there is also often a contribution at various levels from black hole driven AGN. Eight VLBA detections have JWST/NIRCam counterparts, predominantly early-type, bulge-dominated galaxies, which we use to get an estimate of the redshift and star formation rate (SFR). Wide-field Infrared Survey Explorer colors indicate that VLBA detections are either AGN or intermediate-disk-dominated systems, while VLBA nondetections correspond to extended, star-forming galaxies. We compare SFRs derived from previous SCUBA-2 850 μ m observations with new JWST-based estimates, and discuss the observed discrepancies, highlighting JWST’s improved capability to disentangle AGN activity from star formation.